Karakteritik Kimia dan Amilograf (Modified Cassava Flour) Singkong Gajah (Manihot utilissima) - Siti Masithah Fiqtinovri (JURNAL AGROINDUSTRI HALAL, 2020)
Singkong gajah (Manihot utilissima) is a tuber crop that contains high carbohydrates but its use in food industry is still less when compared to ordinary cassava. Until now there have been many studies on the characteristics of mocaf of ordinary cassava, such as time of fermentation, yeast concentration, and drying techniques, but no one has examined further of the characteristics of mocaf of singkong gajah (MSG), especially in terms of its amylographic properties. This study aims are to examine the chemical characteristics and amilographs of elephant cassava (MSG) mocafs, and compare them to commercial flour. Singkong gajah was fermented using 0.25% yeast of tape by the weight of singkong gajah chips and soaked for 16 hours. Data displayed are based on dry weight and all analyzes were performed in three replications and the results are presented as mean values. MSG contains 0.84% of crude fiber; 84.44% of starch; 2853 cP of peak viscosity value ; 3199 cP of breakdown viscosity ; 680 cP of viscosity of setback ; and 77.10oC of temperature of gelatinization. The high viscosity and resistance to retrogradation and the low temperature of gelatinization indicate that MSG can be applied to cream or sauce soup products, which in the process and the final product requires a very thick starch.